G. N. LEECH - Principles of Pragmatics - Michael R. Scott (Ilha do Desterro)
'0 Leão é manso e justo para quem faz tudo direito...' Income tax notice, Brazil 1984. One of the problems for both linguistics and for users of anguage lies in the difference between what is said and what is meant. As users of language we have to learn that Você não quer me dar uma mãozinha? is not an odd request for information about someone's negative wishes but, by implicature, a request for action -- and that it has nothing to do with transplant operations. One of the jobs of linguistics, and one which has been swept under the carpet until fairly recently, is to elucidate how it is that we can produce and understand such utterances as (1). This is why Professor Leech's book is so timely. Pragmatics, for Leech usefully defined.as the study of how utterances have meanings in situations (Preface, x) attempts in a systematic way to find out and set down the principles behind certain choices in language which govern situational meaning.